2016
DOI: 10.1080/17474086.2016.1205479
|View full text |Cite
|
Sign up to set email alerts
|

Management of pregnant chronic myeloid leukemia patients

Abstract: Data published and informations acquired in terms of fertility, conception, pregnancy, pregnancy outcome and illness control for all the approved TKIs will be reviewed, as well as suggest how to manage a planned and/or unplanned pregnancy/conception. Literature search methodology included examination of PubMed index, meeting presentations, and updated Investigator's brochures and data files of TKIs companies. Expert commentary: Male patients trying to conceive apparently have no limitation in the use of TKIs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 67 publications
2
46
0
Order By: Relevance
“…Nilotinib does not cross the placenta in a significative concentration and does not seem to be teratogenic, but data are limited. A recent review summarized reported cases and provided recommendations of management of pregnancy in CML; so far no case of pregnancy in a CML patient associated with bosutinib and ponatinib therapy has been described 22. However, as in our case, treatment is not always mandatory; it is necessary if white cell count exceeds 100×10 9 /L and platelet count exceeds 500×10 9 /L, as reported by Milojkovic and Apperley 23.…”
Section: Discussionsupporting
confidence: 57%
“…Nilotinib does not cross the placenta in a significative concentration and does not seem to be teratogenic, but data are limited. A recent review summarized reported cases and provided recommendations of management of pregnancy in CML; so far no case of pregnancy in a CML patient associated with bosutinib and ponatinib therapy has been described 22. However, as in our case, treatment is not always mandatory; it is necessary if white cell count exceeds 100×10 9 /L and platelet count exceeds 500×10 9 /L, as reported by Milojkovic and Apperley 23.…”
Section: Discussionsupporting
confidence: 57%
“…We cannot deny that imatinib therapy during pregnancy is associated with an increased risk of spontaneous abortions and serious congenital malformations. Abruzzese et al (2016) recently presented a complete review on the subject; they suggested that treatment with TKIs has no limitations in male patients trying to conceive, while effective contraception should be encouraged in all female patients because of the risk of fetal complications associated with drug exposure. Conception should be planned and TKI therapy discontinued in female patients during pregnancy, and individual risks need to be considered when an unplanned pregnancy occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Since Pye et al first reported the outcomes of 180 female patients exposed to imatinib during pregnancy , more evidence has accumulated to indicate the potential embryotoxic and teratogenic effect of TKIs including imatinib , nilotinib , and dasatinib during pregnancy. Currently, for female patients with CML wishing to consider pregnancy, it is accepted that at least an MMR should be achieved prior to conception, and patients should remain off TKI during pregnancy, especially during the crucial first trimester . As to the specific degree and duration of the response that should be achieved before planned pregnancy, there is no consensus.…”
Section: Discussionmentioning
confidence: 99%